Studying of the effect of temperature and culture media on growth of fungus Darluca filum (Biv.)Cast. Isolated from Puccinia coronata Corda. Parasitoid on Avena sterilis L. L. - النقار رحاب (Latakia University Journal -Biological Sciences Series, 2024)
Abstract.Darluca filum (Biv.)Cast. was isolated from rust fungus Puccinia coronata Corda. parasitoid on Avena sterilis L. The effect of temperatures 15, 20, 25, 30, 35 C° was studied on the growth of D.filum and its ability to produce and germinate conidia. The optimum temperature for growth mycelium was 35C°, and the optimum degree for sporulation and germination was 30 C°, and germination decreased at temperatures 20 C°. The fungus was able to produce conidia at temperatures from 20-35 C°, and the highest production was at the temperature 30 C° and 25 C°, reached 1.32x 106 spores/ml and 1.13x 106 spores/ml, respectively. The effect of different media (PDA, SDA, MEA, PGA) on the growth of D.filum was studied under the influence of a constant temperature of 25±1 C°. The results showed that the growth of mycelium was the fastest on MEA culture, and the results showed ability of D.filum to produce spores on all studied cultures with Significant differences between some cultures, and no significant differences others, the fungus gave the best production on SDA culture with 1.532x 106 spores/ml, the highest germination rate was on MEA and PDA cultures, and it ranged between 79.6% and 65% on straight.